Gyrodactylus marinus infecting the gill filaments of farmed and wild Atlantic cod in Norway - Haugen, Pål (Universitetet i Tromsø, 2009)
Cod aquaculture is a rapidly expanding industry in Norway and with an increase of biomass in mariculture the concern for diseases spread to and from farmed populations of cod is increasing. The genus Gyrodactylus Nordmann, 1832 are parasitic monogeneans infecting teleost fish in marine and fresh water habitats worldwide. To investigate a possible problematic species of this genus the gill filaments of Atlantic cod, Gadus morhua L. were examined for parasites. Both farmed and wild caught cod were sampled from Ålesund, Kvarøy, Brønnøysund and Øksfjord Norway. From these samples a total of 48 specimens of Gyrodactylus sp. were investigated through morphological and molecular techniques. The opisthaptoral hard parts from each individual were compared through morphology and measurements and all specimens were found to have a similar morphology. The ITS1 and ITS2 together with the 5.8S subunits from rDNA were compared between the specimens investigated and confirmed the observed morphological homogeneity All species were found to be Gyrodactylus marinus Bychowsky and Poljansky 1953. Furthermore untreated farmed cod have a higher prevalence of G.marinus than what is found in wild cod populations.